Role of Optical Coherence Tomography on Corneal Surface Laser Ablation - Bruna V. Ventura; Haroldo V. Moraes; Newton Kara-Junior; Marcony R. Santhiago (Journal of Ophthalmology)
This paper focuses on reviewing the roles of optical coherence tomography (OCT) on corneal surface laser ablation procedures. OCT is an optical imaging modality that uses low-coherence interferometry to provide noninvasive cross-sectional imaging of tissue microstructure in vivo. There are two types of OCTs, each with transverse and axial spatial resolutions of a few micrometers: the time-domain and the fourier-domain OCTs. Both have been increasingly used by refractive surgeons and have specific advantages. Which of the current imaging instruments is a better choice depends on the specific application. In laser in situ keratomileusis (LASIK) and in excimer laser phototherapeutic keratectomy (PTK), OCT can be used to assess corneal characteristics and guide treatment decisions. OCT accurately measures central corneal thickness, evaluates the regularity of LASIK flaps, and quantifies flap and residual stromal bed thickness. When evaluating the ablation depth accuracy by subtracting preoperative from postoperative measurements, OCT pachymetry correlates well with laser ablation settings. In addition, OCT can be used to provide precise information on the morphology and depth of corneal pathologic abnormalities, such as corneal degenerations, dystrophies, and opacities, correlating with histopathologic findings.